Whether niche changes promote the evolution of species: a case study of Paeonia in Asia and North America - Wang, Yihui; Chen, Yuan; Prijic, Zeljana; Markovic, Tatjana; Lyu, Yingmin; Tian, Caihuan; Zhang, Xiuxin (Frontiers in Plant Science, 2024)
Ecological changes have been observed to promote rates of lineage diversification, yet the precise roles of ecological factors, species evolution, and environmental variability in driving species diversity remain research hot spots. The association between ecological change and lineage diversification, particularly with regard to the size of the time scale, remains poorly understood. To explore whether ecological change facilitates species evolution, we focused on the unique family Paeoniaceae, which encompasses both herbaceous and woody taxa, to investigate the evolutionary rates. As a unique family characterised by a single genus of angiosperms and comprising various climatic types, the ecological niche changes of Paeoniaceae are closely associated with the evolution, making it an ideal model for conducting association analysis. In this study, we integrated the molecular fragments and ecological factors to explore the relationship between species evolution and niche changes in Paeoniaceae. The phylogenetic tree revealed that Paeoniaceae forms a sister relationship with Penthoraceae, Haloragidaceae, Iteaceae, Crassulaceae, and Saxifragaceae, constituting an independent clade based on the positive selection of molecular fragments including two protein-coding genes and eight non-coding regions. The divergence time was estimated to be between 102 and 116 Mya (Million years ago). The phylogenetic tree within Paeonia revealed a clear division into three groups: sections of Paeonia, Moutan, and Onaepia with high support values for each branch based on the ten positive selection of molecular fragments. The rapid rate of evolution observed in Paeonia, about 0-5 Mya. In addition, ecological niche modeling showed that the potential distributions for Paeonia expanded from middle Asia to eastern Asia, and from central North America to the Northern part of North America during the Last Glacial Maximum (LGM) to Mid Holocene (MID) period. This suggests that Paeonia continuously adapted to changing ecological environments over time. Compared to the rate of climatic niche divergence and lineage diversification, the ecological niche of Paeonia underwent significant changes during the period of 3-11 Mya, occurring 5 Mya earlier than the period of evolutionary rate change. These findings offer comprehensive insights into the relationship between niche change and the evolution of species, providing valuable perspectives for further ecological cultivation efforts.